Patterns of regional and distant metastasis in esthesioneuroblastoma. (10th February 2016) - Banuchi, Victoria E.; Dooley, Laura; Lee, Nancy Y.; Pfister, David G.; McBride, Sean; Riaz, Nadeem; Bilsky, Mark H.; Ganly, Ian; Shah, Jatin P.; Kraus, Dennis H.; Morris, Luc G. T.
Abstract : Objectives/Hypothesis: To define the incidence and risk factors of metastatic disease and the effectiveness of salvage therapy in esthesioneuroblastoma (ENB). Study Design: Retrospective analysis of 57 patients presenting from 1979 through 2009. Methods: Cumulative incidence of neck failure, distant failure, and survival were assessed using the Kaplan‐Meier method. Results: Overall survival for all patients was 85% at 5 years and 75% at 10 years. Overall survival was negatively impacted by intracranial tumor extension ( P < 0.001), positive resection margins ( P = 0.05), and neck metastases ( P = 0.017). Neck lymph nodes were not routinely electively irradiated during this time period. Nodal metastases developed in 17% of patients at a median time of 60 months. Kadish stage was not associated with a risk of nodal metastasis ( P = 0.78). After treatment for nodal recurrence, locoregional control was achieved in 78% of patients. Of patients developing nodal recurrence, more than half developed distant metastases. The cumulative incidence of distant metastasis was 39% at a median time of 40 months. Patients who presented with Kadish stage C or D had a significantly increased risk of distant failure ( P < 0.001). In patients developing nodal ( P = 0.017) or distant metastasis ( P = 0.001), the probability of survival was significantly decreased. Conclusion: Regional and distant metastases in patients with esthesioneuroblastoma occur in a delayed fashion and negatively impact survival. Neck nodal recurrence may be a harbinger of distant metastases. At the Memorial Sloan Kettering Cancer Center, New York, New York, we now treat the majority of ENB patients with elective nodal irradiation. However, the chief obstacle to long‐term cure is distant metastases. Level of Evidence: 4. Laryngoscope, 126:1556–1561, 2016